WORK FAMILY CONFLICT AMONG MEDICAL OFFICERS AT MALAYSIAN PUBLIC HOSPITALS - Abdul Razak, Ahmad Zainal Abidin bin; Yeop Yunus, Nek Kamal bin; Mohd Nasurdin, Aizzat (International Business Education Journal, 2010)
This study examined the relationship between work overload and job involvement within two dimensions of work-family conflict [ work interference with family (WIF) and family interference with work (FIW). The sample comprised of 391 local doctors working full-time in nineteen public hospitals in Peninsular Malaysia. Statistical results using regression analysis indicated that work overload was positively related to both work interference with family (WIF) and family interference with work (FIW). On the other hand,job involvement was found to have no significant impact on the two forms of work-family conflict. Implications of the results,limitations, and future research directions are also presented.